Response surface methodology for glucose conversion by applying deep eutectic solvent (DES) as green solvent - Romaito, Rizki Falah; Wulandari, Dini; Utami, Syelvia Putri; Aziz, Yelmida (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2024)
Glucose is a monosaccharide-type carbohydrate that serves as a fundamental building block of biomass. In this research, glucose was hydrolyzed using a Deep Eutectic Solvent (DES) as the solvent and AlCl3 as the catalyst. The effects of temperature and catalyst concentration were investigated as key variables in the reaction. The glucose conversion results were tested using the UV-Vis spectrophotometer. The yields of glucose conversion were analyzed using the Response Surface Methodology (RSM) with Design Expert Version 13 software. The results of RSM analysis show that glucose conversion increases linearly with rising reaction temperature. The effect of catalyst concentration indicates that glucose conversion decreases at higher catalyst levels. The reaction temperature and AlCl3 catalyst concentration that can be recommended for optimum conditions from the Design Expert data processing results are 112.869 C and 1.913% with a predicted conversion value of 93.844%.